Peer effects and health impacts of different body cognitive biases in children: micro evidence from China - Zhang, Yun; Wang, Xueying; Zhu, Weiqiang (Frontiers in Public Health, 2024)
Background: In China, children commonly display body cognitive biases, which constitute a significant yet hidden public health issue. These biases potentially jeopardize children's well-being, hinder the cultivation of human capital, and impede societal progress. However, limited research employs theoretical analysis and econometric testing to investigate the formation of different body cognitive biases among Chinese children and their health impacts.: Based on a local average network model for theoretical analysis, this study utilizes a sample of 4289 children from four phases of the China Health and Nutrition Survey (CHNS) conducted from 2004 to 2011. Utilizing Logit and IV Probit models, systematically evaluate the peer effect, heterogeneity of effects, and health impacts of children's different body cognitive biases.Results: 1) The peer effect contributes to the development of light-and heavy-body cognitive biases in Chinese children. 2) The heterogeneity analysis shows that the peer effect of body cognitive biases is more significant in rural and female children. 3) The influence of heavy-body cognitive bias is more pronounced in adolescent children. 4) The "eating-activity balance" is disrupted by the two body cognitive biases in children, leading to deviations from normal body type. 5) Specifically, the light-body cognitive bias leads children to intake more and burn fewer calories, increasing their risk of obesity. 6) Conversely, the heavy-body cognitive bias prompts children to intake less and expend more calories, resulting in a higher prevalence of thinness.Discussion: This study innovates by exploring peer effects on body cognitive biases in Chinese children, elucidating their direction and health implications. While overweight and obesity are recognized as overt health issues, the spread and impact of implicit issues like body cognitive biases should not be overlooked. Nevertheless, the issue is largely neglected in developing countries, such as China, where existing children's health policies are inadequate in addressing it. Promoting accurate body image perception and understanding of health prevention strategies among children requires adequate attention to peer effects.